Signature of selection to improve effectiveness of genomic selection in temperate x tropical breeding populations - CGIAR Research Program on Maize (2019)
We have identified and established key collaborations and identified a talented PhD candidate who is able to carry out the project. We have identified a set of appropriate populations within a key breeding program in Africa to test the hypotheses.